Nonpenetrating Deep Sclerectomy as an Effective Treatment of Glaucoma Related to Familial Amyloid Polyneuropathy. Issue 5 (June 2015) - Latasiewicz, Marta; Millá, Elena; Giralt, Juan; Molina, Juan Jose; Matas, Jessica
<x xml:space="preserve">Abstract</x> Purpose: To present the clinical course and treatment by nonpenetrating deep sclerectomy (NPDS) of open-angle glaucoma secondary to familial amyloid polyneuropathy (FAP). Patients and Methods: In a series of 10 patients with FAP in a tertiary ophthalmology center, 4 eyes of 3 patients required glaucoma filtration surgery and NPDS with implant, and local intraoperative mitomycin C application was performed. Intraocular pressure and anatomic bleb functionality were measured. We performed a retrospective review of data from medical charts of the 10 FAP patients, which included demographics, incidence and treatment of glaucoma, and previous vitrectomy. Results: NPDS resulted in normalization of intraocular pressure in all 4 eyes. Ten eyes (6 patients) of the studied group underwent vitrectomy because of amyloid opacities, 7 eyes (4 patients) had glaucoma, 6 of the eyes with glaucoma were previously vitrectomized, and 4 of them subsequently required glaucoma surgery. Conclusions: NPDS is an effective treatment of FAP glaucoma. Previously vitrectomized eyes have a more severe course of glaucoma and more frequently require filtration surgery.